2023
DOI: 10.3390/insects14030213
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Habitat Suitability Models for Four Ticks of Medical Concern in Illinois, USA

Abstract: The greater U.S. Midwest is on the leading edge of tick and tick-borne disease (TBD) expansion, with tick and TBD encroachment into Illinois occurring from both the northern and the southern regions. To assess the historical and future habitat suitability of four ticks of medical concern within the state, we fit individual and mean-weighted ensemble species distribution models for Ixodes scapularis, Amblyomma americanum, Dermacentor variabilis, and a newly invading species, Amblyomma maculatum using a variety … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…A different sampling approach would likely be necessary to capture the small amounts of residual tick DNA spread across a large grass field or forest plot. This consideration particularly applies to I. scapularis , a specie currently more abundant in the northern third of the state (Kopsco et al., 2023; Rydzewski et al., 2011, 2012), and is relatively scant in central and southern Illinois, where our sampling occurred, compared to the other three species.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A different sampling approach would likely be necessary to capture the small amounts of residual tick DNA spread across a large grass field or forest plot. This consideration particularly applies to I. scapularis , a specie currently more abundant in the northern third of the state (Kopsco et al., 2023; Rydzewski et al., 2011, 2012), and is relatively scant in central and southern Illinois, where our sampling occurred, compared to the other three species.…”
Section: Discussionmentioning
confidence: 98%
“…Collection sites were characterized by a mix of three habitat types: open prairie, mowed prairie or forest edge, and mixed deciduous understory. These habitats included preferential environments within the state for each of the three targeted tick species and have documented tick presence (Bacon et al., 2022; James et al., 2015; Kopsco et al., 2023). Three 250 m linear transects were established at each site (one transect per habitat type) and sampled for both ticks and plant matter via a block random design (without replacement) to reduce bias (i.e., one of the three transects was selected at random for each site per visit, for a total of three visits per site on average throughout the field season; Figure 1b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in TBD cases has coincided with the geographic range expansion of the medically important vector tick species Ixodes scapularis , Amblyomma americanum , Amblyomma maculatum and Dermacentor variabilis [ 7 ]. Previous research found that factors associated with climate change, such as maximum average temperature and total precipitation [ 8 ], presence of forest cover in metropolitan areas [ 9 ] and wetlands [ 10 ], open habitats with minimal canopy cover [ 11 ] are associated with distribution and abundance of various tick species in Illinois. Thus, the number of tick species and cases of TBDs in the Upper Midwest region is likely to follow an upward trend in the coming decades.…”
Section: Introductionmentioning
confidence: 99%
“…Human disease incidence is known to depend upon the distribution and abundance of established populations of infected tick vectors (Falco et al., 1999; Pepin et al., 2012), yet the spatial distribution of tick populations is highly variable. Landscape and habitat suitability studies have found associations between I. scapularis abundance or presence with habitat features such as forest cover and soil type in the midwestern United States (Gardner et al., 2020; Kopsco et al., 2023), but there is often no clear relationship with a major host for the juvenile stages, white‐footed mice (Guerra et al., 2002). Movement patterns have also been difficult to reconstruct, though there is evidence that I. scapularis spatial expansion can be relatively rapid (Clow et al., 2017), despite the fact that ticks are flightless and crawl only a few metres (Daniels & Fish, 1990), pointing to the importance of host‐associated transport in their dispersal.…”
Section: Introductionmentioning
confidence: 99%